2014
DOI: 10.1097/aud.0000000000000073
|View full text |Cite
|
Sign up to set email alerts
|

Automated Screening for High-Frequency Hearing Loss

Abstract: Objective:Hearing loss at high frequencies produces perceptual difficulties and is often an early sign of a more general hearing loss. This study reports the development and validation of two new speech-based hearing screening tests in English that focus on detecting hearing loss at frequencies above 2000 Hz.Design:The Internet-delivered, speech-in noise tests used closed target-word sets of digit triplets or consonant–vowel–consonant (CVC) words presented against a speech-shaped noise masker. The digit triple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(105 citation statements)
references
References 32 publications
1
92
3
1
Order By: Relevance
“…Vlaming et al (2014) reported a similar correlation with PTA HF of 0.79, and 0.82, for the high frequency triplet and CVC tests, respectively. Jansen et al (2014) compared the broadband French digit triplet test (DTT) with a CVC test in standard speech-shaped noise, and with the CVC test in a LP filtered masking noise.…”
Section: Test Validitysupporting
confidence: 57%
See 3 more Smart Citations
“…Vlaming et al (2014) reported a similar correlation with PTA HF of 0.79, and 0.82, for the high frequency triplet and CVC tests, respectively. Jansen et al (2014) compared the broadband French digit triplet test (DTT) with a CVC test in standard speech-shaped noise, and with the CVC test in a LP filtered masking noise.…”
Section: Test Validitysupporting
confidence: 57%
“…The discriminative power of LP 3 was also reflected in the highest values for sensitivity and specificity, respectively 93 and 94%. The results can be well compared with the results of Vlaming et al (2014). They developed two high frequency (HF) tests, both with a LP filtered speech shaped noise masker, one using digit triplets, and one using CVC words.…”
Section: Sensitivity and Specificity For Hfhlmentioning
confidence: 83%
See 2 more Smart Citations
“…A correction factor was calculated by subtracting this SNR from the average SNR of all digits (Vlaming et al, 2014). The correction factors were applied to the digits to align the 50% correct recognition probabilities for all the digits.…”
Section: Resultsmentioning
confidence: 99%